Coral cover and rubble cryptofauna abundance and diversity at outplanted reefs in Okinawa, Japan - Piera Biondi; Giovanni Diego Masucci; James Davis Reimer (PeerJ, 2020)
Global climate change is leading to damage and loss of coral reef ecosystems. On subtropical Okinawa Island in southwestern Japan, the prefectural government is working on coral reef restoration by outplanting coral colonies from family Acroporidae back to reefs after initially farming colonies inside protected nurseries. In order to establish a baseline for future comparisons, in this study we documented the current status of reefs undergoing outplanting at Okinawa Island, and nearby locations where no human manipulation has occurred. We examined three sites on the coast of Onna Village on the west coast of the island; each site included an outplanted and control location. We used (1) coral rubble sampling to measure and compare abundance and diversity of rubble cryptofauna; and (2) coral reef monitoring using Line Intercept Transects to track live coral coverage. Results showed that rubble shape had a positive correlation with the numbers of animals found within rubble themselves and may therefore constitute a reliable abundance predictor. Each outplanted location did not show differences with the corresponding control location in terms of rubble cryptofauna abundance, but outplanted locations had significantly lower coral coverage. Overall, differences between sites (Maeganeku1, Maeganeku2 and Manza, each including both outplanted and control locations) were significant, for both rubble cryptofauna and coral coverage. We recommend (1) to outplant colonies from more stress-resistant genera in place of Acropora, and (2) to conduct regular surveys to monitor the situation closely. With a lack of baseline data preceding impacts, rigorous monitoring over time can highlight trends towards increases or decreases in evaluated variables, allowing to obtain a clearer idea of the effects of transplants and on the trajectory of impacts due to climate change and local stressors . Finally, we also recommend (3) to establish conservation and sustainable practices that could aid the ongoing restoration efforts such as installing anchoring buoys to reduce impacts from anchoring, which could reduce coral mortality of both outplanted and native coral colonies.